Historical cartographic materials as a source for international and cadastral boundary management in rivers - Srebro, Haim (Proceedings of the ICA, 2018)
International and cadastral boundaries are important for ensuring stable legal territorial matters. This article deals with the long-term location and management of boundaries in rivers and the depiction of the rivers on cartographic materials. A few countries have agreed that the boundary will not follow changes in the river (like in the Mongolia-China Border Treaty), whereas most agree that the boundary will follow slow, natural and gradual changes in the river (like is stated in the Israel-Jordan Peace Treaty). The international boundary under the British Mandate between Palestine and Trans-Jordan in the Jordan and Yarmuk rivers was defined in 1922. The cadastral boundaries were defined in these rivers in the 1930s along the international boundary. For more than 70 years, until the Israel-Jordan 1994 Peace Treaty, the rivers have changed their channels east and westward to distances up to hundreds of meters. During that period the mandatory boundaries in these rivers changed their political status to the armistice lines, the cease-fire lines, and to international boundaries between sovereign states. These lines were usually delineated on topographic maps in the rivers, drawn by cartographers following contemporary map revision. During that entire period the cadastral boundaries were not changed in order to adapt them to the actual position of the rivers and to the delineated international boundaries. Owing to large water works on both rivers, including the construction of dams and diversion channels in order to meet the increasing needs of the population on both sides, the water flow of the rivers decreased dramatically to less than one tenth of the original natural flow. The population today is more than ten times than it used to be under the British Mandate. The changes in the water channels during the last 20 years since the 1994 peace treaty are in the magnitude of 10 meters versus hundreds of meters in the past. In addition, intensive land cultivation adjacent to the river banks has stabilized them. In 2000, due to the construction of a dam on the Yarmuk River, both sides jointly fixed coordinates of the relevant boundary line in the river according to the boundary delineation in the peace treaty. The accumulated artificial changes along both rivers have cancelled their natural behavior and have influenced the changes in the river channels. This may justify an initiative to fix the boundary lines in both rivers by coordinates according to the peace treaty delimitation, enabling the cadastral boundaries to be fixed according to the fixed international boundary line. The article analyzes boundary line management in changing rivers in light of development of the legal approach and practice from the time of the Romans until today. It analyzes the special case of the boundary line in the Jordan and Yarmuk rivers, and introduces a proposal for stabilizing this boundary line. The research of the changes of these rivers is based on changes in the depiction of their channels on various kinds of maps and cartographic sources, produced through the last century by many producers. They include British, German, ANZAC, Israeli and Jordanian maps and charts. The cartographic materials include large scale field survey sheets and engineering charts from the 1920s, cadastral charts from the 1930s, topographic maps produced through the last century and orthophoto maps produced since the 1990s, including joint Israeli-Jordanian orthophoto and charts produced by the Joint Boundary Commission as part of the peace agreement and its implementation. The article includes a variety of cartographic examples.